Adjacent Wake Effect of a Vertical Axis Wind Turbine. (2015) - Chowdhury, Harun; Mustary, Israt; Loganathan, Bavin; Alam, Firoz
Abstract: The main objective of this study is to understand the effect of turbine placement and surrounding structures. Using Urban Green Energy's UGE-4K vertical axis wind turbine and the ANSYS computational fluid dynamics package (CFX), a dynamic fluid analysis was undertaken looking at the wake of the turbine through a variety of different inlet speeds and rotational frequencies to determine suitable flow recovery for optimal placement of subsequent turbines. The results showed that the wake interference is minimal at around 5 times the diameter of the turbine downstream. Results also show that flow recovery was a lot slower to the right of the turbine especially along a line 15° from the centre of the turbine to the right as this is coincident with the vortices generated from the turbines rotation.